Edukasi Pencegahan Diare Pada Anak di Kelompok Dasawisma Kelurahan Kenali Asam Bawah - Ariyanto Ariyanto; Tina Yuli Fatmawati (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2021)
Deaths due to diarrhea in Indonesia have decreased. Although the mortality rate has decreased sharply, the morbidity rate is still quite high. The duration of diarrhea and the frequency of diarrhea in acute patients cannot be reduced. The highest number of diarrhea cases in Jambi Province in 2017 was in Jambi City, amounting to 11,326 cases. The purpose of this community service is to increase public knowledge about preventing diarrhea in children. This activity was carried out in August 2020 at one of the residents' houses in the Dasawisma group at RT 047 in Kenali Asam Bawah. The target is 15 mothers with children aged 1 to 12 years. The methods used were lectures, discussion / question and answer with mothers about the prevention of diarrhea using leaflets and supplementary feeding in the form of milk, bread and cereals. After the extension activities are carried out, participants understand about the prevention of diarrhea in children and will apply what the extension team has said so that the child's health will be maintained optimally. It is recommended that parents need to equip themselves a lot with various knowledge by participating in extension activities or looking for information in print / online media related to efforts to improve children's health